"There is no order in which God calls us": The Depiction of Christianity and Christians in the Netflix Series Squid Game - Bosman, Frank (Journal for religion, film and media, 2022)
The highly successful and also somewhat controversial Netflix series Squid Game takes a very critical stance on the - supposed - intimate relationship between South Korean Christianity and capitalism, especially regarding what is known as the ‘prosperity gospel’. The series features some explicitly Christian characters who do not act according to what they preach, that is, they behave explicitly egoistically instead of altruistically. The series even seems to suggest that ‘true’ Christian compassion and self-sacrifice are to be found outside the boundaries of institutionalized Christianity rather than among nominal Christians. In this article, the author explains in more detail this twofold criticism that the series gives regarding (South Korean) Christianity by carefully examining key scenes and figures from the series, and positioning the series within South Korean (religious) society.